Reconfirmation and Molecular Characterization of MRSA & MRSE Isolates - Kum, Siau Ling (2017)
The treatment of diseases related to antibiotic resistance is becoming difficult due to the rapid development of antibiotics-resistant strains. Methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) are some of the common antibiotics-resistant bacteria that are spreading rapidly in the hospitals and communities. The methicillin resistance of MRSA and MRSE is mainly due to the formation of penicillin binding protein 2a (PBP2a) encoded by mecA gene that is not inhibited by beta-lactam antibiotics. The mecA gene in MRSA is carried by staphylococcal cassette chromosome mec (SCCmec) and it classified into five major types; I-V. The aim of this study was to identify the types of SCCmec among the MRSA isolates, and to confirm the presence of mecA gene in the possible MRSE isolates as well as to determine the DNA extraction method that yield better quality and quantity of DNA. In this study a total of 35 isolates isolated by Chuah (2016) from healthy individuals at INTI International University were analysed using confirmatory tests such as gram-staining, catalase test, MSA, Brilliance MRSA 2 Agar, and antibiotics susceptibility testing. Two DNA extraction methods; crude extraction and i-genomic BYF DNA Extraction Mini Kit were used in this study and compared. PCR was conducted on genomic DNA from possible MRSE isolates to detect the mecA gene. Furthermore, multiplex PCR was conducted on genomic DNA from confirmed MRSA isolates to identify the types of SCCmec. From the confirmatory tests, out of total 35 isolates, 4 were confirmed by MRSA and 6 isolates were possibly MRSE. This study also shows that –genomic BYF DNA extraction Mini Kit yielded better quantity and quality of DNA than crude extraction based on the bands produced by agarose gel electrophoresis and the spectrophotometer analysis. Result from the PCR and SCCmec typing showed no amplification of mecA gene in all the possible MRSE isolates. Furthermore, the SCCmec types could not be identified from the MRSA isolates as no amplification of the specific genes. There are various factors could have contributed to the failure of detecting mecA gene and types of SCCmec.